NEGARA PARIPURNA DAN AKSI MASSA: IMPLIKASI BAGI KESADARAN POLITIK MAHASISWA DI UNIVERSITAS JEMBER - Natasya, Aurellia; Mrr Ratna Endang Widuatie; Muhammad Albar Syafikri; Sheilla Gita Ramadhani; Tarish Aulia Rasyidah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The study aims to analyze the implementation of values in the yudi latif's state parliament book and tan malaka's mass action book on the thought and critical consciousness of Jember University students. They presented national ideas, political morality, and a complementary spirit of social struggle in shaping the intellectual character of the younger generation. Research data are collected through the Google form questionnaires and descriptive analyses to describe student responses tendencies and use correlation tests to assess variable relationships. Studies have shown that students' understanding of national and social worth of struggle fall into high categories and affect their critical, reflective, and heightened social concern in the context of college life. The findings point out that integration of value education, political reinforcement of literacy, and open dialogue among college students is necessary for the internalization of national values and critical consciousness to develop in a balanced, deep, and sustained environment in higher education and to have a positive impact on student development.